Chemical composition and foliage production of Erythrina americana (Fabaceae) in living fences during two climatic seasons - Oliva Hernández, Jorge; López Herrera, María Aurelia; Castillo Linares, Erika Belem (Revista de Biología Tropical, 2021)
Introduction: Erythrina americana is a tree legume found as part of the fence of livestock farms of the tropical region. However, sheep farmers do not routinely or strategically use the foliage of this type of legume as a dietary supplement due, in part, to ignorance of its chemical composition and foliar performance, as well as the factors that affect them. Objective: To determine the influence of season and diameter of E. americana tree on the chemical composition and foliage yield at a 90-day regrowth age. Methods: 47 trees were used in a two-factor design. The factors were season (dry and rainy) and tree diameter at 0.20 m above ground level (D-9 between 0.05 and 0.09 m and D-13, between 0.091 to 0.13 m). The response variables were dry matter production and crude protein from foliage (kg árbol-1). Results: The season did not affect (P > 0.05) the production of dry matter and crude protein. However, the diameter of E. americana affected them (P < 0.01). In diameter D-13, the highest production of dry matter and crude foliar protein tree-1 was detected with respect to D-9. Conclusions: The diameter of the tree had a more influence than the season on yield of dry matter and crude protein.